KONSEP PAJAK DI INDONESIA DALAM EKONOMI ISLAM MENURUT PEMIKIRAN IBNU KHALDUN - Barokallah Barokallah; Gustiya Sunarti; Fatimah Yunus (Fakultas Ekonomi Universitas Prof. Dr. Hazairin, SH. Bengkulu, 2025)
Ibn Khaldun argued that excessive taxes imposed on the people would lead to a decline in economic activity, which would also result in a decline in the country's economy. The role of taxes has not yet answered or met the needs of the people, for example, road infrastructure, many roads are damaged and have not been repaired, bridge facilities are still lacking, resulting in hampered distribution of goods and causing prices to soar. This type of research is library research. The realization of tax revenue reached IDR 2,842.5 trillion or 101.4% of the 2024 State Budget target or grew by 2.1% year on year (yoy). The poverty rate is 8.47% with a population of 23.85 million poor people. The poverty rate in Indonesia is still dominated by rural areas at 11.03%, this is higher than the poverty rate in urban areas at 6.73%. Indonesia's regulatory policies are in accordance with Ibn Khaldun's concept, but their implementation has not had a significant impact, because state revenue grew 2.1% but extreme poverty is still very large at 8.47%.